2019
DOI: 10.1002/gch2.201900068
|View full text |Cite
|
Sign up to set email alerts
|

Mussel‐Inspired Adhesive Polydopamine‐Functionalized Hyaluronic Acid Hydrogel with Potential Bacterial Inhibition

Abstract: etc. Among them, hyaluronic acid (HA)derived hydrogel is one of the ideal candidates due to its inherent biological homology, feasible structure modification, as well as good degradability. [9,10] The high water retention capacity and high viscoelasticity of HA also allow it to be suitable for wound dressings.To construct desirable HA-based hydrogels, different strategies have been established. Relying on the intermolecular noncovalent interactions, the physical cross-linking HA hydrogels emerged. Rodell et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This was because the PDA functionalization introduced abundant reactive catechol groups having high binding affinity to the diverse nucleophiles (e.g., amines, thiols, and imidazoles) of peptides and proteins on the cell surfaces. In the previous studies, PDA-modified HA was generally prepared based on EDC/NHS method [ 50 , 51 ] or thiol-prefunctionalized HA [ 52 , 53 ]. The efficiency of these chemical modifications is limited in terms of the low substitution of catechol groups and tedious preparation process, resulting in insufficient grafting ratio of catechol groups and a fast degradation rate of HA due to chain broken during grafting process.…”
Section: Discussionmentioning
confidence: 99%
“…This was because the PDA functionalization introduced abundant reactive catechol groups having high binding affinity to the diverse nucleophiles (e.g., amines, thiols, and imidazoles) of peptides and proteins on the cell surfaces. In the previous studies, PDA-modified HA was generally prepared based on EDC/NHS method [ 50 , 51 ] or thiol-prefunctionalized HA [ 52 , 53 ]. The efficiency of these chemical modifications is limited in terms of the low substitution of catechol groups and tedious preparation process, resulting in insufficient grafting ratio of catechol groups and a fast degradation rate of HA due to chain broken during grafting process.…”
Section: Discussionmentioning
confidence: 99%
“…They also synthesized HA-DA by EDC/NHS, and added polydopamine-coated reduction graphene oxide for hydrogels using the horseradish peroxidase (HRP)/hydrogen peroxide (H 2 O 2 ) system [ 27 ]. What's more, many other works also have shown that DA grafting onto hyaluronic acid molecules could enhance the adhesion ability of hydrogels [ [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels prepared by physical methods usually have poor stability and are easy to degrade. The hydrogel prepared by chemical method has good mechanical properties, for example, the hydrogels prepared by dopamine and thiol hyaluronic acid through Michael addition reaction have good tissue adhesion in vitro, but the introduction of transition metal ions or exogenous coupling agents usually leads to cytotoxicity [ 31 ]. The enzymatic crosslinking method allows the reaction to be carried out under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the mussels’ biological events, several approaches have been followed to improve the hydrogel adhesion by optimizing the surface chemistry and hydrogel matrix. Biomimetic moieties containing catechol units [ 24 , 25 , 26 ], polydopamine [ 27 , 28 ], polyelectrolytes [ 8 , 29 , 30 ], and reactive chemical groups like N -hydroxysuccinimide (NHS) [ 31 , 32 ] were incorporated into the hydrogels to enhance adherence. Barrett et al reported that the hydrogel of PEO-PPO-PEO endcapped with catechols [ 33 , 34 ] adhered to hydrated tissue surfaces.…”
Section: Introductionmentioning
confidence: 99%